Interactional Feedback on English Proficiency: Grammatical Awareness - Amiruddin; Adzim, Syahrun; Sadat Malik, Anwar; Badru, Nurhidayanti (ETDC: Indonesian Journal of Research and Educational Review, 2022)
This study examines whether or not interactional feedback has a considerable positive impact on first-year MA Nurul As'adiyah Callacu students' grammatical awareness. The pre-experimental research method was used in the study. 38 grade X A students made up the sample. The research's pre- and post-test grammatical data were collected, and the t-test in SPSS was used to assess it. The study's findings showed a substantial difference between the students' levels of grammatical awareness on the pretest and posttest. The fact that the mean posttest score was greater than the mean pretest score (91.32 > 59.08) served as evidence. These mean scores were different in a statistically significant way. The probability value is lower than the significant level (0.00 < 0.05), which was based on the t-test value at the significant level of 0.05. Based on the result analysis, it can be said that interactional feedback significantly improved grammatical awareness in the first year of MA Nurul As'adiyah Callacu because it promoted learners' intellectual operations and thought processes, which led them to reflect on ideas, particularly in grammar learning.